STUDY REGARDING THE CORRELATION BETWEEN THE ACADEMIC AND PROFESSIONAL ENVIRONMENT FROM THE PERSPECTIVE OF FUTURE GRADUATES. MANAGERIAL ACCOUNTING CASE - TĂNASE, Gabriela Lidia; ȘTEFĂNESCU, Aurealia (Annales Universitatis Apulensis Series Oeconomica, 2014)
In a turbulent economic environment, characterized by a downward trend of financial resources and jobs offer, professional environment requirements are increasing, and thus, the academic environment’s role is becoming major. These were the coordinates that have directed our empirical research on analyzing the perspective of future graduates regarding the correlation between the academic and professional environment in the field of managerial accounting. The research approach considers on one hand, a synthesis of ideas published on this subject in the literature. This is complemented by an empirical study based on a questionnaire to which we have received responses from future graduates of the academic environment in the accounting field. The study results showed that all respondents believe that accounting education is correlated with the professional environment, the academic environment offering them the necessary training in managerial accounting for a successful integration into the professional environment. The majority of respondents also believes that for the integration in the professional environment, future graduates must hold simultaneously theoretical and practical knowledge, but also organizational skills. The results reveals that, by their relevance, the factors that motivate future graduates to prepare in managerial accounting are: the interest to acquire knowledge, labor market integration, discipline content, professor’s teaching methods, the promotion of the exam. Also, all respondents would accept to participate in volunteer programs organized by the professional environment in order to gain experience in managerial accounting. Regarding the adaptation of the managerial accounting approach in the academic environment, most respondents support a moderate adjustment by implementing internship and volunteering programs.